A Testing Strategy With Adaptive Dose Selection and Two Endpoints. (3rd July 2018) - Glimm, Ekkehard; Bezuidenhoudt, Mauritz; Caputo, Angelika; Maurer, Willi
ABSTRACT: The article deals with the design of a complex clinical trial with multiple doses of an experimental treatment tested against a control treatment, interim analyses and several endpoints characterizing treatment success. The closed test principle, methods from group sequential testing, and combination test methodology are combined to control the familywise error rate (FWER) when testing for treatment benefit. We also discuss strategies for utilizing the correlations between some of the relevant test statistics.